Redescription of two species of Coelotanypus (Kieffer) 1913 (Diptera: Chironomidae) in rivers of the Parano-Platense basin (Argentina, South America) - Paggi, Analía C.; Zilli, Florencia (Zootaxa, 2018)
Male imagos of Coelotanypus delpontei (Edwards) are redescribed and newly figured and the immature stages are described and figured for the first time. During this study, male imagos of C. mendax (Lynch Arribalzaga) are also redescribed. The specimens were collected from the Paraná and near Uruguay rivers in the Parano-Platense basin.